The history of neuroscience - Rooney, Anne (History of science (Rosen Publishing Group), 2018)
Highlights the history of neuroscience from the first records from Greek anatomists to modern studies of artificial intelligence and brain control. Includes a timeline, a glossary, resources for further information, and color photographs.